Fe2P4O12-carbon composite as a highly stable electrode material for electrochemical capacitors - Soni, Roby; Kurungot, Sreekumar (New Journal of Chemistry, 2019)
Supercapacitors are important energy storage devices for high power applications. Carbon materials, metal oxides and conducting polymers have been known to show capacitive charge storage but transition metal phosphates are not as well-known as electrode materials in supercapacitors. In this study, an iron cyclotetraphosphate (Fe2P4O12)-carbon composite has been synthesized and demonstrated as an electrode material for supercapacitors. The Fe2P4O12-carbon composite has been thoroughly characterized by X-ray photoelectron spectroscopy, Raman spectroscopy, X-ray diffraction, electron microscopy, etc. The composite shows predominant capacitive behaviour only in acidic medium; its charge storage properties are relatively poor in alkaline medium, indicating the important role of H+ in the charge storage mechanism. The composite shows a capacitance of 251 F g(-1) at a current density of 1 A g(-1). The composite is highly stable in 0.5 M H2SO4 and does not show any apparent capacitance loss after 9000 charge-discharge cycles recorded at a current density of 5 A g(-1).

FeNx/FeSx-anchored carbon sheet-carbon nanotube composite electrocatalysts for oxygen reduction - Bhange, Siddheshwar N.; Soni, Roby; Singla, Gourav; Ajithkumar, T. G.; Kurungot, Sreekumar (ACS Applied Nano Materials, 2020)
Even though various Pt-free electrocatalysts for oxygen reduction reaction (ORR) have been introduced, many of them are found to be active only in alkaline conditions. Considering Nafion, phosphoric acid-doped polybenzimidazole (PBI), and so on as the prominent ionomer membranes, used in the commercially available polymer electrolyte membrane fuel cells (PEMFCs), it becomes important that any development on the Pt-free catalysts should ensure the better ORR performance under acidic conditions. The present work effectively tackles this issue, where an ORR-based catalyst could be prepared with simultaneous incorporation of both Fe-N and Fe-S active sites on in situ generated carbon sheets which are spatially separated by the carbon nanotube (CNT) network. This catalyst shows ability to perform under both acidic and basic conditions. This has been achieved by growing a polyethylenedioxythiophene polymer network in the presence of CNT and melamine followed by its pyrolysis under an inert atmosphere. The catalyst formed at 900 degrees C (PMCNT-900) displays 0.94 V onset potential for ORR under acidic electrolyte conditions, which corresponds to 60 mV overpotential compared to its 40 wt % Pt/C counterpart. Interestingly, in single cell demonstration of Nafion-based PEMFC with PMCNT-900 as the cathode catalyst, the system delivered a maximum power density (PD) of 500 and 275 mW/cm(2) at 60 degrees C under H-2-O-2 and H-2-air feed conditions, respectively. On the other hand, in a single cell test in the anion exchange membrane fuel cell (AEMFC) mode, a maximum power density of 65 mW/cm(2) at 50 degrees C could be achieved with the same cathode catalyst, which is a comparable value obtained while employing Pt/C as the cathode. These results, thus, infer to the efficiency of the catalyst to facilitate ORR under the extreme pH conditions, and particularly its performance under acidic condition reveals its prospect as a potential Pt-free electrocatalyst to serve in the Nafion-based systems.
Keywords: carbon nanotube; electrocatalyst; fuel cell; oxygen reduction reaction; Pt-free ORR